A morphological study on variation in branching pattern of dorsalis pedis artery and its clinical perspectives - Vengadesan, B. (International Journal of Advances in Medicine, 2020)
Background: The study of dorsalis pedis artery and variations in its branching pattern has been reported sporadically. The purpose of this study was to evaluate the arterial. Supply on the dorsum of the foot. Methods: The study was carried out of forty dissected limbs of unknown sex and age from the department of Anatomy, Aarupadai veedu Medical College, Pondicherry. Results and Discussion: The incidence of classical text-book description was found to be very less in present study. In 5% of cases the dorsalis pedis artery was replaced by the peroneal artery. In 5% of cases the anterior tibial artery was found on lateral side of leg, dorsalis pedis artery is a continuation of the anterior tibial artery seen passing above lateral malleolus and then it passes forwards along the lateral side of the dorsum of the foot. Conclusion: The findings suggest that the lateral aspect of the dorsum of the foot has a poor nourishment.